2020
DOI: 10.1093/rheumatology/keaa264
|View full text |Cite
|
Sign up to set email alerts
|

Femoral vein wall thickness measurement: A new diagnostic tool for Behçet’s disease

Abstract: Objectives Diagnosing Behçet’s disease (BD) is a challenge, especially in countries with a low prevalence. Recently, venous wall thickness (VWT) in lower extremities has been shown to be increased in BD patients. In this study, we aimed to investigate the diagnostic performance of common femoral vein (CFV) thickness measurement in BD and whether it can be used as a diagnostic tool. Methods . Patients with BD (n = 152), ankylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 20 publications
2
14
1
Order By: Relevance
“…VWT was especially increased among those BS patients with no apparent vascular involvement suggesting that VWT could be an early indication of vascular inflammation (66,71). Furthermore, Alibaz et al suggested that VWT could be used as a distinctive diagnostic tool for the differentiation of BS from other inflammatory diseases (68). A letter to the editor (72) commented on these findings and suggested that an overestimation of diagnostic accuracy and absence of external validation were the main issues in this study.…”
Section: Vascular Involvementmentioning
confidence: 69%
See 1 more Smart Citation
“…VWT was especially increased among those BS patients with no apparent vascular involvement suggesting that VWT could be an early indication of vascular inflammation (66,71). Furthermore, Alibaz et al suggested that VWT could be used as a distinctive diagnostic tool for the differentiation of BS from other inflammatory diseases (68). A letter to the editor (72) commented on these findings and suggested that an overestimation of diagnostic accuracy and absence of external validation were the main issues in this study.…”
Section: Vascular Involvementmentioning
confidence: 69%
“…Clinical significance is unclear since no diseased controls were included and the data is based on diagnosis codes, carrying the risk of misdiagnosis. Growing evidence indicates that venous wall thickness (VWT) of the lower extremity veins is increased in BS compared to that found in several inflammatory diseases and healthy controls (66)(67)(68)(69)(70)(71). VWT was especially increased among those BS patients with no apparent vascular involvement suggesting that VWT could be an early indication of vascular inflammation (66,71).…”
Section: Vascular Involvementmentioning
confidence: 99%
“…79 In the former case, fibrinogen becomes prothrombotic, 80 and in the latter case lysine residues mediate the formation of aggregates instead of cross-links, thus weakening elastic fibers, which makes arteries prone to aneurysm formation. 81 Excess HC may induce proliferation of vascular smooth cells, 82 a phenomenon which should be counteracted by H 2 S 83 : the loss of the biological activity of H 2 S and GSH may contribute to the observed venous 84 and arterial thickening 85 of BD and may favor the emergence of oculo-vascular disease. 86 Our meta-analysis has several limitations: (1) we could not verify whether smoking impacted on the overall heterogeneity; (2) given that methotrexate may inhibit the MTHFR gene transcription, 87 we could not evaluate whether methotrexate use impacted on the overall heterogeneity, as 32 studies did not quote whether patients were taking MTX or not; (3) we could not assess whether plasma HC was persistent or transient, as studies were all cross-sectional and not prospective; (4) we could not explore the impact of other underrepresented clinical manifestations of BD on plasma HC; (5) a better interpretation of plasma HC in thrombotic BD would have required a control group with thrombosis due to other reasons, and none of the studies in the systematic review had considered this issue; (6) although our metaanalysis was performed on comparable and compatible observational studies, we cannot discount a degree of publication bias, the evaluation of which by an empirical graphical method can be misleading 14,15 and inadequate for observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…79 In the former case, fibrinogen becomes prothrombotic, 80 and in the latter case lysine residues mediate the formation of aggregates instead of cross-links, thus weakening elastic fibers, which makes arteries prone to aneurysm formation. 81 Excess HC may induce proliferation of vascular smooth cells, 82 a phenomenon which should be counteracted by H 2 S 83 : the loss of the biological activity of H 2 S and GSH may contribute to the observed venous 84 and arterial thickening 85 of BD and may favor the emergence of oculo-vascular disease. 86…”
Section: Discussionmentioning
confidence: 99%
“…This measurement may even facilitate the differentiation between inflammatory bowel disease and gastrointestinal involvement of BS. It may hint at a subclinical involvement of major vessels (veins) in all patients with BS independently of the clinical phenotype and may represent a new diagnostic tool (38,39).…”
Section: Venous Manifestationsmentioning
confidence: 99%